From Colonization to High Production and Plasmodium vivax Infection of Anopheles darlingi and Anopheles deaneorum: a Platform for Malaria Research - Maisa Araujo; Alice Andrade; Alessandra Bastos; Najara Santos; José Pontual; Jéssica Araújo; Marina Rocha; Maria Miguel; Ana Costa; Joseph Vinetz; Ricardo Gazzinelli; Jansen Medeiros (Bio-Protocol)
The mass rearing of anopheline mosquitoes under laboratory conditions is essential for advancing malaria research. It facilitates in-depth studies on mosquito biology, behavior, and genetics and their role in Plasmodium transmission. However, the colonization of Neotropical anophelines such as Anopheles darlingi—a primary malaria vector in the Amazon region—has proven particularly challenging due to its unique reproductive characteristics. Unlike other species that can initially be colonized using forced copulation methods and later adapt to natural mating, An. darlingi does not copulate under forced conditions. Recent breakthroughs in An. darlingi colonization have been achieved using flashlight induction techniques, which have enabled the establishment and maintenance of stable laboratory populations. These advancements have created new opportunities for vector control studies in Brazil, including the testing of innovative control methods and Plasmodium transmission-blocking strategies. This protocol offers a comprehensive, step-by-step guide for initiating and scaling up large laboratory colonies of An. darlingi and An. deaneorum, a secondary malaria vector. It details methods for copulation induction, colony management, and successful artificial infection of mosquitoes with Plasmodium vivax. The guide serves as a critical resource for establishing new Neotropical anopheline colonies from different populations, contributing to future malaria research and control efforts in the Amazon. Additionally, the establishment of Brazil’s first Malaria Vector Production and Infection Platform (Plataforma de Produção e Infecção de Vetores da Malária, PIVEM) has further supported the development of new control technologies and the study of P. vivax–Anopheles interaction, advancing efforts to combat malaria in the region.